'Dead letters! … Dead men?': the rhetoric of the office in Melville’s ‘Bartleby, the scrivener’ - Thompson, Graham (Cambridge University Press, 2000)
Although a good deal of recent critical attention to Melville's writing has followed the lead of Robert K. Martin in addressing the issue of sexuality, the predominant themes in discussions of “Bartleby” remain changes in the nature of the workplace in antebellum America and transformations in capitalism. But, if one of the abiding mysteries of the story is the failure of the lawyer–narrator to sever his relationship with his young scrivener once Bartleby embarks upon his policy of preferring not to, it is a mystery that makes sense within both of these critical discourses. On the one hand, the longevity of the relationship dramatizes a tension implicit in Michael Gilmore's suggestion that the lawyer–narrator straddles the old and the new economic orders of the American market-place. Although he may employ his scriveners “as a species of productive property and little else”, his attachment to his employees is overwhelmingly paternalistic and protective. On the other hand, James Creech suggests that Pierre (published the year before “Bartleby”) is a novel preoccupied with the closeting of homosexual identity within the values of an American middleclass family, while Gregory Woods describes Melville as the nearest thing in the prose world of the American Renaissance to the Good Gay Poet Whitman. In this critical context the longevity of the relationship suggests that the lawyer–narrator's desire to know Bartleby, to protect him, to tolerate him, to be close to him, to have him for his own, and then to retell the story of their relationship, needs to be considered in relation to sexual desire.